Beyond Speech: Exploring Visual-Gestural Learning in English Speaking Instruction for Young Learners with Hearing Impairment - Ririn Ambarini (INDO PUBLISHING, 2026)
This study explores the implementation of visual–gestural learning in English speaking instruction for young learners with hearing impairment. Using a descriptive qualitative design, the study involved one English teacher and six young learners with hearing impairment in a special education school in Indonesia. Data were collected through classroom observations, a semi-structured teacher interview, and documentation, and were analyzed using thematic analysis. The findings indicate that visual–gestural learning was implemented through gestures, facial expressions, pictures, sign-supported communication, written words, pointing, and demonstrations. These resources were used to support learners’ understanding of English expressions and facilitate classroom interaction. The learners responded through multiple communication modes, including signing, gesturing, pointing, writing, mouthing English words, and oral responses when possible. The findings also revealed several challenges, including teacher preparation, limited learning materials, differences in learners’ communication abilities, and the need to coordinate multiple visual resources. Nevertheless, visual–gestural learning provided opportunities for greater accessibility, participation, and interaction. The study suggests that English speaking instruction for learners with hearing impairment can move beyond speech-centered practices toward a more inclusive multimodal approach that recognizes visual and gestural communication as meaningful components of language learning.